Carbon isotopic fractionation associated with methylotrophic methanogenesis - Summons, RE; Franzmann, PD; Peter Nichols (1998)
Methanogenesis from 'noncompetitive' substrates such as trimethylamine (TMA) and dimethylsulfide (DMS) may be quantitatively important in global methane budgets. This is because choline, glycine betaine, trimethylamine-N-oxide and related compounds, the precursors of TMA, are produced abundantly and ubiquitously by prokaryotic and eukaryotic organisms, particularly those from marine environments. 'Noncompetitive' substrates may be a particularly important source for the methane which occurs in the surface mixed layer of the ocean at or above saturation levels. In this study, we measured isotopic fractionation factors for methane and polyisoprenoid lipids formed by methanogens utilizing trimethylamine as their principal carbon source. Methanosarcina barked showed isotope effects (ε) of 50.2‰ for the conversion of TMA to methane and 20.2‰ for TMA-biomass. Moreover, phytanyl chains of M. barkeri polar lipids were depleted by as much as 18‰ compared to biomass as was the co-occurring hydrocarbon PME. For the Antarctic methanogen Methanococcoides burtonii we measured even greater ε values of 71‰ (TMA to CH 4), 49.6‰ (TMA to biomass) and 79.9‰ (TMA to phytanyl ether). It should be stressed that these large fractionations represent the maximum or near maximum values possible when the substrate concentrations are non-limiting. The isotopic compositions of methane and methanogen lipid formed by these organisms in natural environments will depend on how completely the substrates are consumed and on how this carbon is partitioned between assimilation and dissimilation processes. The ε values for methylotrophic methane formation measured here are significantly higher than those reported for aceticlastic methanogenesis (approx 21‰) and in the same range as those reported for reduction of carbon dioxide (32 to 79‰). The highly 13C-depleted signature of polyisoprenoid moleties compared to biomass of cultured methanogens suggests that there is significant isotopic fractionation inherent in the lipid ...